2018
DOI: 10.1080/10872981.2018.1478170
|View full text |Cite
|
Sign up to set email alerts
|

Exploring medical students’ barriers to reporting mistreatment during clerkships: a qualitative study

Abstract: Background: Despite widespread implementation of policies to address mistreatment, the proportion of medical students who experience mistreatment during clinical training is significantly higher than the proportion of students who report mistreatment. Understanding barriers to reporting mistreatment from students’ perspectives is needed before effective interventions can be implemented to improve the clinical learning environment.Objective: We explored medical students’ reasons for not reporting perceived mist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 20 publications
2
53
0
1
Order By: Relevance
“…While not a central finding of our study, our analysis also indicated that students are less likely to report episodes of public humiliation or other forms of mistreatment if they perceive that it will negatively impact their grade or prolong the negative experience. This is consistent with the literature on this topic as fear of reprisal and a desire not to undertake the time and effort involved in reporting have been identified as reasons that limit reporting of medical student mistreatment [25]. Participants also recommended that continued education on teaching skills and feedback skills would improve the learning environment; a continued reminder that education and training on these skills should not be undervalued.…”
Section: Discussionsupporting
confidence: 68%
“…While not a central finding of our study, our analysis also indicated that students are less likely to report episodes of public humiliation or other forms of mistreatment if they perceive that it will negatively impact their grade or prolong the negative experience. This is consistent with the literature on this topic as fear of reprisal and a desire not to undertake the time and effort involved in reporting have been identified as reasons that limit reporting of medical student mistreatment [25]. Participants also recommended that continued education on teaching skills and feedback skills would improve the learning environment; a continued reminder that education and training on these skills should not be undervalued.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, this study does not explore in depth the barriers to reporting mistreatment. Chung et al suggest that reporting mistreatment is low due to a myriad of reasons including fear of reprisal, perception of medical culture as well as the difficult logistics of reporting [4]. This study may benefit from more questions focusing on whether these experiences are not being reported due to fear of reprisal or simply due to the difficult logistical nature of reporting.…”
Section: Medical Student Mistreatment: An Inconvenient Truth?mentioning
confidence: 94%
“…Moreover, the context of those experiences is often the clinical environment, which can be hard for universities to monitor and change. Efforts by universities to detect gender discrimination with the currently used instruments such as course evaluations might not be adequate as underreporting is a known problem [41][42][43], and response rates are usually low. As the epidemic of burnout among female medical doctors and students, for example, in Sweden, is a fact [44], we hypothesize that GD/SH experienced during medical education maybe one of the driving forces.…”
Section: Study Implicationsmentioning
confidence: 99%